Use of Antiretroviral Therapy During Pregnancy and Adverse Birth Outcomes Among Women Living With HIV-1 in Low- and Middle-Income Countries: A Systematic Review. (1st September 2018) - Saleska, Jessica Londeree; Turner, Abigail Norris; Maierhofer, Courtney; Clark, Jan; Kwiek, Jesse J.
Abstract : Background: Worldwide, nearly 18 million women of reproductive age are living with HIV-1. Although increased access to antiretroviral therapy (ART) during pregnancy has significantly reduced HIV-1 mother-to-child transmission (MTCT), a similarly robust reduction in preterm birth (PTB) and low birthweight (LBW) among infants born to women living with HIV has not been observed. This study was designed to identify associations between classes of ART regimens and risk of PTB or LBW. Setting: Low- and middle-income countries. Methods: We conducted a systematic review of randomized and observational studies that assessed the effect of ART regimen on the risk of PTB (⩽37 completed weeks of gestation) or LBW (<2500 g at birth) among pregnant women in low- and middle-income countries living with HIV-1. We searched Medline, COCHRANE, Web of Science, SCOPUS, and CPCI-S for included studies. Results: When compared to monotherapy, both nonnucleoside reverse transcriptase inhibitor– and protease inhibitor–based regimens had a consistent, harmful association with LBW. There is mixed evidence suggesting both potential harm and potential benefit for most other regimens on risk of LBW and PTB, and the harmful or protective effects of certain regimens varies depending on the drug backbone. Conclusions: Although the benefits of ART during pregnancy for prevention of MTCT are undisputed, this systematic review indicates that ART regimens vary substantially in their association with LBW and PTB. Although challenging, optimization of ART regimens could simultaneously promote maternal health, prevent MTCT, and also minimize risks of PTB and LBW. Abstract : Supplemental Digital Content is Available in the Text.